Meningkatkan hasil belajar kemampuan gerak dasar manipulatif dengan menggunakan alat bantu pembelajaran sederhana di Sekolah Dasar - Andri Arif Kustiawan; Andy Widhiya Bayu Utomo; Aba Sandy Prayoga; Arief Nur Wahyudi (Journal Power Of Sports, 2019)
The purpose of this research is to improve learning outcomes capability of motion the base of manipulative manner using the tools simple learning to promote disorder to to their students the class iii of state elementary school sdn ploso ii district level pacitan the new school term of 2017 / 2018. The research is research ptk ) ( class action .This study was conducted in two cycles , with each cycle consists of planning , the implementation of , observation , and reflection .A subject of study were students class iii sdn ploso ii district pacitan covering 30 students consisting of 12 students 18 students son and daughter .The data derived from teachers , students , and researchers .Tekhnik data collection is by observation , assessment and documentation .The validity of the data using tekhnik triangulation .Data analysis using tekhnik descriptive based on close analysis of prosentase qualitative. From the result of this research of analysis that was obtained of the initial conditions of students who graduate only 9 a student or 30 % , in the first a notebook detailing the development of students who graduated into 16 there were students or 53,34 % and all that is in second keeps a notebook detailing the students who graduated into 26 students or 86,67 % while 4 other students from getting possessed have not been solved. Drawing conclusions from the study is by using the tools learning simple can improve learning outcomes capability of motion basic manipulative to their students class iii sdn ploso ii kabupaten pacitan years lessons 2017 / 2018 .